The triterpenoid cucurbitacin B augments the antiproliferative activity of chemotherapy in human breast cancer1. Issue 12 (13th December 2012) - Aribi, Ahmed; Gery, Sigal; Lee, Dhong Hyun; Thoennissen, Nils H.; Thoennissen, Gabriela B.; Alvarez, Rocio; Ho, Quoc; Lee, Kunik; Doan, Ngan B.; Chan, Kin T.; Toh, Melvin; Said, Jonathan W.; et al.
Abstract Despite recent advances in therapy, breast cancer remains the second most common cause of death from malignancy in women. Chemotherapy plays a major role in breast cancer management, and combining chemotherapeutic agents with nonchemotherapeutic agents is of considerable clinical interest. Cucurbitacins are triterpenes compounds found in plants of the Cucurbitaceae family, reported to have anticancer and anti‐inflammatory activities. Previously, we have shown antiproliferative activity of cucurbitacin B (CuB) in breast cancer, and we hypothesized that combining CuB with chemotherapeutic agents can augment their antitumor effect. Here, we show that a combination of CuB with either docetaxel (DOC) or gemcitabine (GEM) synergistically inhibited the proliferation of MDA‐MB‐231 breast cancer cells in vitro. This antiproliferative effect was accompanied by an increase in apoptosis rates. Furthermore, in vivo treatment of human breast cancer orthotopic xenografts in immunodeficient mice with CuB at either low (0.5 mg/kg) or high (1 mg/kg) doses in combination with either DOC (20 mg/kg) or GEM (12.5mg/kg) significantly reduced tumor volume as compared with monotherapy of each drug. Importantly, no significant toxicity was noted with low‐dose CuB in combination with either DOC or GEM. In conclusion, combination of CuB at a relatively low concentration with either of the chemotherapeutic agents, DOC or GEM, shows prominent antiproliferative activity against breast cancer cells without increased toxicity. This promising combination should be examined in therapeutic trials of breast cancer.